Valorization of Waste Plastic Bags in Manufacturing of Binders for Bituminous Concrete for Roads Coatings - Kowanou, Houénou; SANYA, EMILE ADJIBADÉ; TCHEHOUALI, DÈFODJI ADOLPHE; DEGAN, GÉRARD; VIANOU, COKOU ANTOINE (My University, 2014)
In 2012, Beninese landfills have quantified more than 12,000 tons plastic wastes with more than 50% of bags. The non-biodegradable nature of plastic generated an unprecedented environmental nuisance. The search for suitable solution led opting for partial recycling through construction processes. This article is devoted to characterization of new bituminous binders built of 50/70 graded bitumen to which is incorporated powder from molten waste plastic bags at 250-280 °C for road coatings/pavement. The analyzed parameters are binder’s penetrability, softening point and adhesiveness, water absorption, Marshall and Duriez stabilities of resulting bituminous concretes. The doped 50/70 graded bitumen, using plastic bags powder at 2-20% (wt/wt.mix), provided bituminous binders of better properties. The recorded results showed that the penetrability decreases when increasing plastic bags content, giving bituminous binders belonging to respective grades of 50/70, 40/60, 35/50, 30/45 and 20/30 following by softening points increase. More the plastic bags content increases, better these binders adhesivity. Similar trend was recorded for stability according Duriez and Marshall on resulting bituminous concretes disclosing the water absorption rate decrease. These obtained good performance characteristics should allow for significant reduction of the rapid degradation of classically coated roads, via extensive usage of waste plastic bags, then decongesting the established landfills here and there in Benin. Keywords: waste plastic bags; bituminous binder; penetrability; softening point; adhesivity; stability; subsidence; bituminous concretes; water absorption rate; compacity.
Keywords: Waste plastic bags; bituminous binder; penetrability; softening point; adhesivity; stability; subsidence; bituminous concrete; water absorption rate; compacity